RETROSPECTIVE SENSITIVITY ANALYSIS OF KOCURIA SPP. TO ANTIBIOTICS - M.O. Faustova; O.A. Nazarchuk; G.A. Loban; Yu.V. Chumak; M.M. Ananieva; V.V. Bondarenko (Проблеми екології та медицини)
Kocuria spp., possessing a powerful arsenal of pathogenicity factors, can cause severe septic conditions in humans under immunodepression. Therefore, it is important to determine the sensitivity of medically important Kocuria spp. to antibiotics. The aim of the study was to conduct a retrospective analysis of the sensitivity of clinical isolates of Kocuria spp. to antibiotics. During 2019-2022, 33 clinical isolates of Kocuria spp. were isolated from patients with odontogenic infectious and inflammatory diseases of the soft tissues of the face. Cultivation for the final identification of microorganisms was carried out according to the standard method. Determining the sensitivity of selected representatives of genus Kocuria to antibiotics was conducted using the disk diffusion method (Kirby-Bauer) according to EUCAST recommendations (v.12.0; 2022). In order to determine the groups of antibiotics to which Kocuria spp. maintain sensitivity, hierarchical cluster analysis was performed using Ward's method. Statistical analysis was performed using standard software IBM SPSS Statistics version 22.0. Among penicillins, representatives of this genus had the highest sensitivity to benzylpenicillin. The sensitivity of Kocuria isolates to cefotaxime and ceftazidime did not differ and was 51.5%. Representatives of genus Kocuria were highly sensitive to meropenem and vancomycin. As a result of research, Kocuria spp. was found to be moderately sensitive to gentamicin. Based on the cluster analysis of antibacterial drugs, according to the sensitivity of isolates of Kocuria spp. to them during 2019-2022, meropenem, benzylpenicillin, ceftazidime, cefotaxime, moxifloxacin, and ciprofloxacin with sensitivity higher than 50.0% were combined. Clinical isolates of Kocuria spp., isolated from patients with infectious and inflammatory diseases of the soft tissues of the face, showed variable sensitivity to all groups of antibacterial drugs during 2019-2022. Representatives of the genus Kocuria show the highest sensitivity to vancomycin. Today, clinical isolates of Kocuria spp. remain sensitive to meropenem, benzylpenicillin, ceftazidime, cefotaxime, moxifloxacin, and ciprofloxacin.